2020
DOI: 10.3991/ijet.v15i22.18197
|View full text |Cite
|
Sign up to set email alerts
|

The Cultivation of Critical Thinking Ability in Academic Reading Based on Questionnaires and Interviews

Abstract: In recent years, Chinese college students have been criticized for having nothing to say, no thinking ability, and lack of critical thinking. Cultivating students' thinking ability is becoming an important task of higher education. Through carrying out questionnaire survey and interviews, the author learned that graduate students' critical thinking skills in academic reading needs to be improved. To improve the situation, it requires joint efforts of teachers and students to improve students' critical thinking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 2 publications
2
11
0
Order By: Relevance
“…Taken as a whole, the results of the current mixed-methods study provide insight into the usefulness of expanding our understanding of the lack of critical thinking skills (abilities) among Chinese international college undergraduates due to China's conventional education system or academic study habits. The study-for-test strategy has a substantial influence on the restricted or nonexistent development of critical thinking abilities among Chinese students, which conforms to the assertion from several studies that there is a lack of knowledge of the definition or idea of critical thinking skills among Asian students (Hood, 2020;Li & Ren, 2020;Jiang, 2020;Kusumastuti et al, 2019;Ghaemi & Mirsaeed, 2017). In addition, the summary of Chinese undergraduates' responses to the critical thinking deposition inventory revealed that absence of speculation is a common problem among Chinese college students, based on the CTDI's items 12: if possible, I try to avoid reading (X = 4.32); 13: decisions made by authority are always right (X = 4.75), item 17: it is interesting to solve difficult problems (X = 1.84, lower than the seldom 2-point Likert scale point).…”
Section: Conclusion and Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Taken as a whole, the results of the current mixed-methods study provide insight into the usefulness of expanding our understanding of the lack of critical thinking skills (abilities) among Chinese international college undergraduates due to China's conventional education system or academic study habits. The study-for-test strategy has a substantial influence on the restricted or nonexistent development of critical thinking abilities among Chinese students, which conforms to the assertion from several studies that there is a lack of knowledge of the definition or idea of critical thinking skills among Asian students (Hood, 2020;Li & Ren, 2020;Jiang, 2020;Kusumastuti et al, 2019;Ghaemi & Mirsaeed, 2017). In addition, the summary of Chinese undergraduates' responses to the critical thinking deposition inventory revealed that absence of speculation is a common problem among Chinese college students, based on the CTDI's items 12: if possible, I try to avoid reading (X = 4.32); 13: decisions made by authority are always right (X = 4.75), item 17: it is interesting to solve difficult problems (X = 1.84, lower than the seldom 2-point Likert scale point).…”
Section: Conclusion and Discussionsupporting
confidence: 84%
“…Several studies by Western academics have shown that Chinese students studying overseas, notably in Thailand, lack critical thinking abilities (Hitchcock, 2017). Simply put, the critical thinking abilities of Chinese students who study overseas have become more important (Li & Ren, 2020;Sun, 2017). The World Economic Forum also published a study in 2010 on the top five talents needed by 2025, which include analytical thinking, critical thinking, active learning, and learning methodologies (Su, 2020).…”
Section: Background Of the Studymentioning
confidence: 99%
“…Critical thinking is thinking clearly and rationally. The ability to think critically is not an inherent ability of humans from birth, but is something that must be trained so that efforts need to be made to improve this ability [42] [43]. Critical thinking has several characteristics [44], namely a) able to analyze arguments, b) able to make a conclusion using inductive/deductive reasoning, c) able to make assessments and evaluations, d) able to make decisions and solve problems.…”
Section: Critical Thinking Abilitymentioning
confidence: 99%
“…Books are the "intellectual food" for college students [1][2][3][4][5][6]. Unlike in senior high school, college students have more extracurricular study time, and reading is their most important extracurricular activity [7][8][9][10][11]. Extracurricular reading can broaden college students' horizons, cultivate their minds and relax their bodies.…”
Section: Introductionmentioning
confidence: 99%